Conceptualizing “Assessment Being Learning”: A Systematic Review of Teacher-Student Collaborative Assessment in China - Cai, Mu Dan; Joseph, Ramanair (International Journal of Religion (IJOR), 2024)
The interconnection between assessment and learning has long been established and remained evolving. To find a localized approach in EFL contexts, this systematic review investigates the existing research on teacher-student collaborative assessment (TSCA) in China, which proposes the integration of assessment, teaching and learning. 55 CNKI-indexed papers from 2016 to 2023 that were relevant to the topic were selected for the review process. This review study summarized the classifications of TSCA application in secondary, high school and tertiary education as well as propositions of teaching models and detected the key elements concerning teachers’ roles, students’ roles and the contextual factors that influence both assessment and learning. By elucidating these diverse components, this review study conceptualized “assessment being learning” aiming to improve the theoretical and practical understanding of TSCA.